Impact of lameness on the milk production of ewes - Baranovič, Štefan; Tančin, Vladimír; Uhrinčať, Michail; Mačuhová, Lucia; Palkovič, Jozef (Acta Agraria Debreceniensis, 2016)
The aim of this study was assessing the impact of lameness on the milk production, somatic cells count and component of milk. We assess also impact of lameness on the order of entry into the milking parlour.The experiment was carried at the farm, located in northern Slovakia. The farm keeps sheep Improved Valachian. Samples of milk were taken during two periods: May, July. It was taken 428 samples together. We recorded three groups by lameness- strong lame, slightly lame, non-lame ewes. We recorded also the order of entry of ewes into the milking parlour in milking row. The results were mathematically processed using the Microsoft Excel program and statistically evaluated by SAS.We found significant statistical differences between months (P